RAP de mulheres e violência patriarcal: sentidos e memória em contradição - Conceição, Karen Silva Santos (2022)
This research focuses on the study of Rap music written by women. The corpus of analysis is composed of the song entitled “Não foi em vão” (2012), by the rapper Lívia Cruz, and the poem “Em legítima defesa” (2012), by Elizandra Souza. The study proposes to observe how the woman enunciates about patriarchal violence, since in the selected clippings we have sayings that respond to the violence that men commit against women. In this way, the general objective of this research is to analyze the selected sayings about violence against women and about women's reaction to patriarchal violence, based on the French Discourse Analysis, anchored in Michel Pêcheux's formulations. In order to do so, the concepts of meaning and memory are articulated in order to perceive the contradictions of the use of violence as a form of defense, a defense that echoes in the corpus as a way of solving patriarchal violence. It also presents an overview of the consolidation of Rap in Brazil, in order to bring the conditions of production of the object of study to the analysis. Still, we seek to make a discussion about patriarchy and for that we bring the authors Saffioti (1987; 1995; 1999; 2015) and Lerner (2019), who make an in-depth study on the influence of patriarchy on violence against women.